Quality of service: a key factor in the competitiveness of transporters: the case of Moroccan operators of International Road Freight Transport - TALMENSSOUR , Kaoutar; CHEBH , Ismail (Revue Internationale des Sciences de Gestion, 2022)
In the context of globalization, companies and governments alike are facing tough and evolving competition. Indeed, in order to survive and make profits, it is imperative to remain "competitive" on the external and internal markets and to offer a superior service quality to that of competitors. This paper is part of an attempt to conceptualize "service quality" in the context of road freight transport. Its objective is to identify the importance of the "quality of service" dimension in determining the competitiveness of carriers, and to outline the elements that make up this dimension. The research consists of a theoretical overview describing the reference framework and a qualitative study based on semi-structured interviews with 12 IRFT (International Road Freight Transport) companies and 9 exporting companies. The results of the research confirm that the quality of service remains the key factor of competitiveness of Moroccan TIRM operators serving Europe. Indeed, service quality in the TIRM consists of the provision of safe, reliable and efficient transport services, including the use of new equipment and technological facilities as well as a variety of services provided, among others.